Legal Consequences of Mixed Marriage Document Falsification In Indonesia (Case Study of Jessica Iskandar and Ludwig Franz Willibald) - Rizza Nafaani Hidayat; Rahtami Susanti; Ika Ariani Kartini (UMPurwokerto Law Review, 2021)
AbstractForgery of letters/documents can be interpreted as an act that has the aim of imitating, creating an object that is no longer original or making an object lose its validity. Mixed marriages are regulated in Article 57 of Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning Marriage. For the marriage to be registered, the conditions such as marriage documents must be met. If there is a forgery of mixed marriage documents, the marriage can be annulled. The cancellation of mixed marriages has an impact on the legal status of the marriage and the parties involved. Cases of falsification of mixed marriage documents that have occurred in Indonesia are those of the artist Jessica Iskandar who falsified her mixed marriage documents. The purpose of this study is to find out the legal consequences of falsifying mixed marriage documents in Indonesia (case studies of Jessica Iskandar and Ludwig Franz Willibald) and legal protection for children born. The research method used is normative juridical, namely through literature studies which examine mainly secondary data in the form of laws and regulations, agreements or contracts, other legal documents, research results, study results, and other references.Keywords: Document Forgery, Mixed Marriage